2018
DOI: 10.1038/s41590-017-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid chromatin repression by Aire provides precise control of immune tolerance

Abstract: Aire mediates the expression of tissue-specific antigens in thymic epithelial cells to remove dangerous self-reactive T lymphocytes. However, the mechanism that allows expression of tissue-specific genes at levels that prevent harm is unknown. Here we show that Brg1 generates accessibility at tissue-specific loci to impose central tolerance. We found that Aire harbors an intrinsic repressive function that restricts chromatin accessibility and opposes Brg1 across the genome. Aire exerted this repressive influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 70 publications
6
71
0
Order By: Relevance
“…However, supportive evidence that this might be expected to be the case was provided by the observation, which we have expanded upon in this study, that the chromatin patterns around AIRE-induced genes in mouse ENCODE ChIP-seq data derived from non-TEC cell types are similar to those observed in mTEC hi ( 3 ). This suggests that AIRE is not required to establish the chromatin architecture of tissue specific antigens but instead acts dynamically to ensure appropriate levels of histone modifications, as suggested by a previous chromatin in vivo assay ( 8 ). Our machine learning approaches support the fact that AIRE status can be predicted from chromatin signatures in both mTEC lo and mTEC hi .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, supportive evidence that this might be expected to be the case was provided by the observation, which we have expanded upon in this study, that the chromatin patterns around AIRE-induced genes in mouse ENCODE ChIP-seq data derived from non-TEC cell types are similar to those observed in mTEC hi ( 3 ). This suggests that AIRE is not required to establish the chromatin architecture of tissue specific antigens but instead acts dynamically to ensure appropriate levels of histone modifications, as suggested by a previous chromatin in vivo assay ( 8 ). Our machine learning approaches support the fact that AIRE status can be predicted from chromatin signatures in both mTEC lo and mTEC hi .…”
Section: Discussionmentioning
confidence: 83%
“…Mutations in AIRE result in the development of multi-system autoimmune disease in humans ( 5 ). Recently other genes, including Fezf2, Prdm1 , and Brg1 , have also been identified to regulate PGE ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aire binds only weakly and nonspecifically to DNA, and no common sequence motif has been identified for Aire target genes 11,12 . Recent chromatin immunoprecipitation experiments suggest that Aire recognizes general epigenetic features and alters chromatin structure including superenhancer and Polycomb-repressed regions, which may lead to indirect regulation of multiple target genes [13][14][15][16] . This idea is further supported by the stochastic nature of target gene expression at a single cell level 15,17,18 , and the variance of Aire-dependent target genes depending on the cell type 19 .…”
mentioning
confidence: 99%
“…Aire has been demonstrated to contribute to the establishment of self-tolerance by optimizing the expression of TRAs by mTECs by employing various transcriptional pathways in a cell-intrinsic manner (14,37,38). The present study has revealed a novel mechanism by which heterogeneity and/or diversity of mTECs can be also created in an Aire-dependent but cell-extrinsic manner: Aire + mTECs functioned in trans to maintain Ly-6C/Ly-6G + mTECs.…”
Section: Discussionmentioning
confidence: 65%